Evaluation of sites for the location of WEEE recycling plants in Spain - Queiruga, Dolores (Waste management (New York, N.Y.), 2008)
As a consequence of new European legal regulations for treatment of waste electrical and electronic equipment (WEEE), recycling plants have to be installed in Spain. In this context, this contribution describes a method for ranking of Spanish municipalities according to their appropriateness for the installation of these plants. In order to rank the alternatives, the discrete multi-criteria decision method PROMETHEE (Preference Ranking Organisation METHod for Enrichment Evaluations), combined with a surveys of experts, is applied. As existing plants are located in North and East Spain, a significant concentration of top ranking municipalities can be observed in South and Central Spain. The method does not present an optimal structure of the future recycling system, but provides a selection of good alternatives for potential locations of recycling plants